Metamorphosis of Collaborative Governance: Designing an Integrated Model for Sustainable Marine Tourism in Teluk Kupang, Indonesia - Dewi, Ida Ayu Lochana; Benu, Fredrik L.; Pandie, David. B.W.; Sayrani, Laurensius P. (Journal Public Policy, 2025)
The Teluk Kupang Marine Nature Park (TWAL) in East Nusa Tenggara, Indonesia, represents a valuable marine conservation area with significant potential for sustainable tourism. However, its management faces persistent challenges, including conflicts of interest among stakeholders, environmental degradation, bureaucratic fragmentation, and centralized governance that limits local participation. This study aims to develop and evaluate a collaborative governance model that addresses these barriers and supports sustainable marine tourism. Using a mixed-methods design, the research combines surveys, in-depth interviews, stakeholder analysis, and document review to explore governance dynamics and stakeholder perceptions. The findings reveal that fragmented collaboration, unresponsive bureaucracy, and limited institutional capacity have constrained effective management. To overcome these challenges, the study introduces the Integrated Collaborative Governance Metamorphosis Model (ICGMM), which emphasizes decentralization, participatory decision-making, and capacity building as prerequisites for effective collaboration. The model outlines a transformation pathway from fragmented governance toward integrated, inclusive, and adaptive management practices. Results indicate that strengthening transparency, aligning conservation and tourism objectives, and empowering local communities are critical for achieving long-term sustainability. This study contributes theoretically by advancing collaborative governance through the metamorphosis concept and offers practical insights for policymakers and conservation managers seeking to balance ecological protection and economic development in marine protected areas.